Moderating Effects Of Insecure Attachment Styles On The Relationships Between Social Networking Site (Sns) Use And Anxiety And Depressive Symptoms - Kondratenko, Kseniia (2023)
This study applied various analyses including Pearson correlation to test relationships between all of the variables, One-way ANOVA to test SNS use effect on anxiety and depressive symptoms, linear regression to test the effect of attachment on anxiety and depressive symptoms, ordinal logistic regression to test the effect of attachment on SNS use and Hayes Process 4 analysis for the moderator analyses. The study findings suggested that depressive symptoms were significantly predicted by SNS use, attachment avoidance and attachment anxiety. SNS use was not predicted by attachment anxiety and attachment avoidance. The study also observed that only attachment anxiety marginally moderated the relationship between SNS use and depressive symptoms.